Effects of Feed Type and Culture System on Growth and Survival of Panulirus homarus Puerulus in Situbondo, East Java - Hendra Hendra; Abdul Rahem Faqih; Mohammad Fadjar; Lailatus Silfiyah (Universitas Islam Lamongan, 2026)
Lobster (Panulirus homarus) aquaculture in Indonesia remains limited due to suboptimal feed management and culture systems, resulting in low growth and survival rates. This study aimed to evaluate the effects of different feed types and culture systems on growth performance, survival rate, feed efficiency, amino acid content, and carbonic anhydrase enzyme activity in lobster puerulus. The study was conducted using a factorial randomized block design with two factors: culture media (bottom cage, floating cage, and fiber tank) and feed types (kijing clams, trash fish, and shrimp head waste). Each treatment was replicated three times at a stocking density of 30 individuals per square meter. The results showed that the highest survival rate (90%) and best feed conversion ratio (6.6) were obtained in fiber tanks with kijing clam feed. The highest growth performance (5.11 g) and enzyme activity were recorded in fiber tanks with shrimp head waste feed. Amino acid content, particularly leucine, was also highest under the same treatment. Statistical analysis indicated that both feed type and culture system significantly influenced lobster performance, with strong relationships observed between feed composition and physiological responses. The conclusion is that the combination of appropriate feed and a controlled culture system is essential for improving lobster aquaculture performance. Fiber-based systems with high-quality feed provide optimal conditions for growth, survival, and metabolic activity, supporting more efficient and sustainable lobster farming.